(untitled) - Neville Woolf (London)
The book has been written with the latter objective particularly in mind and this new edition gives a thorough grounding in the scientific basic of pathology, whist recognizing the need to link this with clinical conditions. This book will prove to be invaluable to the medical undergraduate in pre-clinical and clinical years, and will also be useful for the cardidate reading for Part I of Membership or Fellowship examinations
Keywords: pathology